Recent trends in cartilage regenerative medicine and its application to oral and maxillofacial surgery. Issue 1 (19th May 2012) - Hoshi, Kazuto; Fujihara, Yuko; Asawa, Yukiyo; Nishizawa, Satoru; Kanazawa, Sanshiro; Sakamoto, Tomoaki; Watanabe, Makoto; Ogasawara, Toru; Saijo, Hideto; Mori, Yoshiyuki; Takato, Tsuyoshi
Abstract: Greater progress has been made in the clinical application of cartilage regenerative medicine, compared with that of other organs. A typical example of cartilage regenerative medicine is autologous chondrocyte implantation, in which chondrocytes isolated from the patient's cartilage are cultured and injected into the cartilage defects in a liquid‐ or gel‐form. However, the classic autologous chondrocyte implantation has been applicable to only limited diseases, including focal cartilage lesion. Therefore, we developed "implant‐type" tissue‐engineered cartilage that shows mechanical strength and three‐dimensional shape. This type of tissue‐engineered cartilage uses scaffold composed of atelocollagen hydrogel and poly‐l ‐lactic acid porous material, which is administered with cultured autologous auricular chondrocytes. Its clinical application to nasal deformity of cleft lip and palate patients has been ongoing at present. This review presents an overview of the current situation regarding cartilage regenerative medicine, as well as introducing our research and the development of implant‐type tissue‐engineered cartilage for the cleft‐lip nose. The discussion of the future development of regenerative medicine is also mentioned.